On Human Essence - Fernández Beites, Pilar (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
To offer a response to the challenge posed by the existentialism of M. Heidegger, the present work uses the ontology proposed by X. Zubiri in Sobre la esencia. The work, then, deals with thinking «about essence», but above all, «about human essence», which creates the difficulty raised by existentialism. The difference between «constitutive» and «conditional» proposed by Zubiri is studied in order to highlight the human being’s (and of all living beings in general) character of not being made once and for all. If we designate essence in the classical sense (unalterable essence) as «constitutive», we propose to bring Zubiri’s intuition to its limit by acknowledging another «essential» level, which is the «constitutional». The constitutional is not essential in tradition’s strict sense, but neither is it accidental; it is essential in a new sense, allowing the incorporation of changes in essenceitself. Thus, one arrives at the so-called processive (or dynamic) essences, which, for not being made once and for all, necessarily include their being made.